Analysis Of The Determinants Of Economic Growth In Madura Island - Nadya Aura Wulan Savitri; Mohammad Wahed (International Journal of Community Service (IJCS), 2026)
Regional economic growth is a fundamenal indicator in assessing development performance and community welfare. Madura Island, as part of East Java Province, continues to record a relatively lower level of economic growth compared to other regions. This study aimed to analyze the effects of Local Own-Source Revenue, Intergovernmental Transfers, Capital Expenditure, and Household Consumption on economic growth in Madura Island. This study uses a quantitative method based on secondary data obtained for the period 2020–2024 across four regencies in Madura Island, namely Bangkalan, Sampang, Pamekasan, and Sumenep. Panel data regression is used as the analytical method. The results show that, partially, Local Own-Source Revenue was found to have no significant influence on economic growth in Madura, while Intergovernmental Transfers, Capital Expenditure, and Household Consumption have positive and significant effects. These findings indicate that economic growth in Madura Island remains dependent on central government transfers, the effectiveness of development expenditure, and household purchasing power, while the role of local revenue has not yet been optimal.